Case Report: Major right-sided hepatectomies in infants in Uzbekistan: a case series - Semash, K.; Dzhanbekov, T.; Islomov, S. (Frontiers in Pediatrics, 2025)
IntroductionLiver resection is a critical surgical option for managing benign and malignant tumors, including rare and complex cases in pediatric patients. While such procedures are well-documented in adults, the surgical management of large liver neoplasms in infants poses unique challenges due to anatomical and physiological considerations, as well as the limited number of cases reported globally.AimThis study aimed to describe the initial experiences with major hepatectomies in infants with large liver neoplasms at our center.Materials and methodsFrom December 2023 to May 2024, four major hepatectomies were performed in pediatric patients aged 5 to 11 months. Indications, perioperative data, and surgical outcomes were retrospectively analyzed.ResultsThe outcomes of the four patients in this case series demonstrate the feasibility and safety of major hepatectomies in infants with large liver neoplasms. Among the cases, three involved hepatoblastoma (PRETEXT stages 2–4), and one was an anastomosing hemangioma. Radical resection (R0) was achieved in all cases, with average intraoperative blood loss 120 ml, and only one patient requiring a blood transfusion. Postoperative complications were minimal, with two cases of mild to moderate post-hepatectomy liver insufficiency (Clavien-Dindo grades 1–2) and one bile leak (Clavien-Dindo grade 2) that resolved spontaneously. No perioperative mortality or tumor recurrence was observed during a six-month follow-up.ConclusionThese results highlight the success of careful surgical planning, advanced techniques, and comprehensive perioperative management in achieving favorable outcomes for this high-risk patient population.